Psychological profile of laryngectomized patients - Bogdan Popescu; Oana Păun; Răzvan V. Scăunașu; Cristian Bălălău; Șerban V. Berteșteanu (Journal of Mind and Medical Sciences)
Larynx cancer is one of the most susceptible form of cancer susceptible to induce alteration of the patient’s psychological profile due to the social role that the larynx has in communication. Oral communication is severely impaired even after voice rehabilitation of the laryngectomized patients, so that the social rehabilitation is somewhat not only a medical but also a social problem. The psychological profile of these patients is altered in a way that dealing with the disease is sometimes neglected and the interaction with the outside world in terms of oral communication is totally abandoned. The starting point for depression in these cases is the acknowledgement of the disease and is, in some cases, the entire medical environment. Facial scarring, the inability to verbally interact with other human, as well as the presence of the tracheostoma, are all deciding factors in the presence of a low self-esteem for these particular patients. Psychological counseling is a mandatory approach for laryngectomized patients, in order to improve their ability to cope with cancer and providing better recovery chances.